Structural-functional insights and studies on saccharide binding of Sophora japonica seed lectin - Yadav, Priya; Shahane, Ganesh; Ramasamy, Sureshkumar; Sengupta, Durba; Gaikwad, Sushama (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of the Sophora japonica seed lectin (SJL) were studied in detail using bioinformatics and biophysical tools. Homology model of the lectin displayed all the characteristics of the legume lectin monomer and the experimental observations correlated well with the structural information. In silico studies were performed by protein-ligand docking, calculating the respective binding energies and the residues involved in the interactions were derived from LigPlot(+) analysis. Fluorescence titrations showed three times higher affinity of T-antigen disaccharide than N-acetyl galactosamine (GaINAc) towards SJL indicating extended sugar binding site of the lectin. Thermodynamic parameters of T-antigen binding to SJL indicated the process to be endothermic and entropically driven while those of GaINAc showed biphasic process. SDS-PAGE showed post-translationally modified homotetrameric species of the lectin under native conditions. In presence of guanidine hydrochloride (0.5-5.0 M), the tetramer first dissociated into dimers followed by unfolding of the protein as indicated by size exclusion chromatography, fluorescence and CD spectroscopy. Different structural rearrangements were observed during thermal denaturation of SJL at physiological pH 7.2, native pH 8.5 and molten globule inducing pH 1.0. Topological information revealed by solute quenching studies at respective pH indicated differential hydrophobic environment and charge density around tryptophan residues. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Dissociation; docking; Homology model; Ligand binding; Sophora japonica seed lectin; Thermal transitions

Amaranthus caudatus lectin with polyproline II fold: conformational and functional transitions and molecular dynamics - Yadav, Priya; Shahane, Ganesh; Gaikwad, Sushama M. (Journal of biomolecular Structure & Dynamics, 2017)
Polyproline II (PPII) fold, a peculiar structural element was detected in the Amaranthus caudatus seed lectin (ACL) based on far UV circular dichroism spectrum, conformational transitions of the lectin and a distinct isodichroic point in thermal denaturation. It was confirmed by using PolyprOnline database to estimate the percentage of amino acids contributing to PPII fold and showed the values as 13.5% and 13.9% for PROSS and XTLSSTR, respectively. Investigations of the functional and conformational transitions of ACL during thermal, pH and guanidine hydrochloride (GdnHCl) induced denaturation were carried out using biochemical and biophysical techniques and molecular dynamics (MD) simulations approach. The lectin got aggregated at 60 °C with instantaneous structural alterations. The aggregation-prone regions in ACL were predicted using online servers viz. AGGRESCAN, AmylPred, FoldAmyloid and Waltz that were represented by Visual Molecular Dynamics tools. Nine conserved regions were identified by these softwares as being ‘hot-spots’ for aggregation. MD simulation studies of the lectin at 60 °C revealed increase in radius of gyration. The loss of PPII fold in 2.0 M GdnHCl was reversible. The partially unfolded intermediate of ACL with diminished PPII fold formed at pH 1.0 was stable up to 90 °C. The polyproline II fold has been rarely detected in lectins, ACL being the second after the potato lectin.